A study of histopathology of H. Pylori gastritis in relation To H. pylori density in gastric biopsies - Dr. Kalaivani Selvi Subramanian; Dr. J. Jeya Shambavi; Dr. Vinoth Boopathy (Tropical Journal of Pathology and Microbiology, 2019)
Introduction: Helicobacter pylori (H. pylori) is of major concern today and is characterized by mucosal infiltration by neutrophils, mononuclear cells and can cause atrophy and intestinal metaplasia which in long term can predispose to gastric carcinoma or lymphoma. Aims of the study: To evaluate the various histopathological parameters in H. pylori induced gastritis and to correlate with H. pylori density. Materials and Methods: This is a Cross sectional descriptive study conducted in the Department of Pathology and Medicine, which included 50 gastric biopsies that was diagnosed as H. Pylori gastritis for a period of 1 year from January 2017 to December 2017. Histopathological variables like Mononuclear cell infiltration, neutrophilic infiltrate, Atrophy, Density of H. pylori were graded according to updated Sydney system. statistical analysis was done using spearman rank correlation test. Results: There were 50 cases of H. pylori gastritis diagnosed during the study period. The age of the patients ranged from 9 to 75 years with male: female ratio of 2.3:1. Atrophy was seen in 25 cases (50%). Mononuclear cell infiltration was seen in all 50 cases (100%). Neutrophilic activity was seen in all 50 cases (100%). Mild activity was seen in 27 (54%) cases. Moderate activity in 10 (20%) cases and severe activity in 13 (26%) cases. H. pylori density was mild in 29 (58%) cases, moderate in 10 (20%) cases and severe in 11 (22%) cases. H. pylori density showed significant correlation with neutrophilic activity. Conclusion: H. pylori density has significant correlation with severity of neutrophilic activity. Chronic inflammation, metaplasia and atrophy did not show significant correlation with H. pylori density.